Social representations among graduate students on academic writing - Romero González, Alba Naroa; Álvarez Álvarez, Manuela de las Nieves (Íkala, Revista de Lenguaje y Cultura, 2019)
Learning what students think about academic writing becomes a valuable source of information that may significantly contribute to didactic proposals more suitable to educational needs. This study aims to inquire on notion about aca-demic writing among students; whether they are being trained on this subject, and which training they are getting ; and how they perceive themselves as writers since their beginning university studies until now. The target population was made up of 96 students in the Modern Languages program at the University of Deusto. They produced some narratives for the purposes of this cross-sectional qualitative study about students’ social representations. Findings suggest that gaining access to a whole new discursive community poses new challenges for students, face to which academic training is insufficient and inadequate. Moreover, while they may perceive some improvement in their writing performance throughout their career, they do not always attribute it to the education received.